Optical coherence tomography angiography in healthy children: A comparison of macular structure. Issue 4 (July 2022) - Plaitano, Carmen; Periti, Francesca; Guagliano, Rosanna; Bertone, Chiara; Barillà, Donatella; Arpa, Cristina; Tinelli, Carmine; Gallo, Flavio Gioele; Bianchi, Alessandro; Magli, Adriano
Purpose: The purpose of the present study was to investigate the perfusion density (PD) of macular superficial (SCP) and deep capillary plexus (DCP), the size of foveal avascular zone (FAZ) and central macular thickness (CMT) in healthy children using optical coherence tomography angiography (OCT-A). Patients and methods: About 206 eyes of 111 children were analyzed. The correlation of gestational age (GA), birth weight (BW), age, sex, refractive errors, and visual acuity (VA) with OCT-A parameters were investigated. Results: The mean PD of the fovea and the mean FAZ area of SCP were 17.1% (DS: 4.26) and 234.47 (DS: 106.39) µm 2 . The mean PD of the fovea and the mean FAZ area of DCP were 13.5% (DS: 5.23) and 298.32 (DS: 112.37) µm 2 . Superficial and deep FAZ areas were not correlated with sex, age, BW, refractive errors, or VA. FAZ area of SCP was correlated with foveal PD ( r  = −0.76) and with CMT ( r  = −0.68). FAZ area of DCP was correlated with foveal's PD ( r  = −0.61). There was no correlation between CMT and refractive errors. Conclusion: OCT-A may provide a non-invasive and reliable approach to evaluate macular perfusion in children. As the FAZ area, PD, and CMT change during the growth period, we performed established a reference range for different ages.